Education and military leadership a study of the R.O.T.C. - Lyons, Gene M. 1924-2013; Masland, John W. (John Wesley) 1912-1968 (Princeton legacy library, 1959)
Rapid turnover of ROTC officers, the decline in ROTC enrollment, inadequate training for the specialized techniques of modem warfare, and the quick obsolescence of technical training have created an acute problem in the development of a body of highly-trained professional career officers. This book takes a fresh view of this vital problem and provides a starting point for a revision of our methods for providing the military leadership that our nation requires.